Phthiocerol Dimycocerosates From Mycobacterium tuberculosis Increase the Membrane Activity of Bacterial Effectors and Host Receptors - Augenstreich, Jacques; Haanappel, Evert; Sayes, Fadel; Simeone, Roxane; Guillet, Valérie; Mazeres, Serge; Chalut, Christian; Mourey, Lionel; Brosch, Roland; Guilhot, Christophe; Astarie-Dequeker, Catherine (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis (Mtb) synthesizes a variety of atypical lipids that are exposed at the cell surface and help the bacterium infect macrophages and escape elimination by the cell’s immune responses. In the present study, we investigate the mechanism of action of one family of hydrophobic lipids, the phthiocerol dimycocerosates (DIM/PDIM), major lipid virulence factors. DIM are transferred from the envelope of Mtb to host membranes during infection. Using the polarity-sensitive fluorophore C-Laurdan, we visualized that DIM decrease the membrane polarity of a supported lipid bilayer put in contact with mycobacteria, even beyond the site of contact. We observed that DIM activate the complement receptor 3, a predominant receptor for phagocytosis of Mtb by macrophages. DIM also increased the activity of membrane-permeabilizing effectors of Mtb, among which the virulence factor EsxA. This is consistent with previous observations that DIM help Mtb disrupt host cell membranes. Taken together, our data show that transferred DIM spread within the target membrane, modify its physical properties and increase the activity of host cell receptors and bacterial effectors, diverting in a nonspecific manner host cell functions. We therefore bring new insight into the molecular mechanisms by which DIM increase Mtb’s capability to escape the cell’s immune responses.